OPINIONS ON THE IMPROVEMENT OF DOMESTIC AND INTERNATIONAL PROMOTION OF TOURIST OFFER FROM SAINT GEORGE - Erika KULCSÁR (Revista de Turism: Studii si Cercetari in Turism, 2011)
A very important factor and  with direct implications in the process of development of the existing tourism potential is the marketing activities related to the promotion of tourist offer both domestically and internationally. Knowledge from direct source of the opinions of managers and directors of the most important tourist locations providing tourism services - hotels and hostels - imposed the achievement of a qualitative marketing research. The qualitative research was conducted in Sfântu Gheorghe. This paper contains the vertical and horizontal analysis of the eight subjects interviewed. The qualitative marketing research aims at knowing the opinions of managers of hotels and hostels in Sfântu Gheorghe on their promotional activity over time in the future.